The Political Economy of the Mental Health System: A Marxist Analysis - Moncrieff, Joanna (Frontiers in Sociology, 2022)
The present paper analyses the functions of the mental health system in relation to the economic organisation of society, using concepts derived from Marx’s work on political economy and building on previous critiques. The analysis starts from the position that mental health problems are not equivalent to physical, medical conditions and are more fruitfully viewed as problems of communities or societies. Using the example of the United Kingdom, it traces how a public mental health system evolved alongside capitalism in order to manage the problems posed by people whose behaviour was too chaotic, disruptive or inefficient to participate in a labour market based on exploitation. The system provided a mixture of care and control, and under recent, Neoliberal regimes, these functions have been increasingly transferred to the private sector and provided in a capitalistic manner. Welfare payments are also part of the system and support those less seriously affected but unable to work productively enough to generate surplus value and profit. The increased intensity and precarity of work under Neoliberalism has driven up benefit claims at the same time as the Neoliberal state is trying to reduce them. These social responses are legitimised by the idea that mental disorders are medical conditions, and this idea also has a hegemonic function by construing the adverse consequences of social and economic structures as individual problems, an approach that has been particularly important during the rise of Neoliberalism. The concept of mental illness has a strategic role in modern societies, therefore, enabling certain contentious social activities by obscuring their political nature, and diverting attention from the failings of the underlying economic system. The analysis suggests the medical view is driven by political imperatives rather than science and reveals the need for a system that is more transparent and democratic. While the mental health system has some consistent functions across all modern societies, this account highlights one of the endemic contradictions of the capitalist system in the way that it marginalises large groups of people by narrowing the opportunities to make an economic contribution to society.